+0  
 
0
40
1
avatar

Simplify the following (2y-1)(4y^{10}+2y^9+4y^8+2y^7 + y^6) Express your answer as a polynomial with the degrees of the terms in decreasing order.

 Jul 28, 2022
 #1
avatar+13809 
+1

Simplify

 

Hello Guest!

 

\((2y-1)(4y^{10}+2y^9+4y^8+2y^7 + y^6)\\ =y^6(2y-1)(y^4+2y^3+4y^2+2y+1)\\ =y^6(2y-1)((8y^3+2y^2+4y+2)y+1)\\ =y^6(2y-1)((((8y+2)y+4)y+2)y+1)\\ =y^6 (2 y - 1) (8 y^4 + 2 y^3 + 4 y^2 + 2 y + 1\\ \color{blue}=16 y^{11} - 4 y^{10} + 6 y^9 - y^6 \)

laugh  !

 Jul 28, 2022

22 Online Users

avatar